The relevance of the national political parties in the context of local party leadership in the Fifth Congressional District of Leyte, 1992-1995 - Pando, Francisco S. (1997)
This study is an attempt to explain the relevance of the national political parties in the context of local party leadership in the Fifth Congressional District of Leyte between 1992 and 1995. It looks on two elements in accomplishing the task, and these are the local party activities. The first element intends to determine the local leaders' relation to the party by examining the aspects of motivation, grasp of ideology, responsibility, loyalty and status. While the second element identifies the political parties' contribution or support to local party activities. This involves the concrete party support such as the financial, organizational, ideological, legal, security, special projects, and others. It also determines the extent of the support in terms of sufficiency of each of the items categorized.
Party processes and relations in the Fifth Congressional District of Leyte reflects the country's kind of politics which is propelled by personality, practicability and material benefits. The local party leaders' basic motivation for membership is primarily monetary as their loyalty and responsibility depends on the benefit they get from the party. The ideological aspect is very less regarded. Complementary to this is the political parties disregard on giving emphasis on the ideological aspect as a significant requisite for membership and over emphasis on financial aspect in forms of party support. This fact encourages politics for convenience complemented with self-interest to develop. This condition in a way portrays a patronage relations binding local party leadership and the political party, in which the party acts as the patron. Thus, reducing the political parties' relevance into just a mere factor in local leadership which veers away from its fundamental status as an institution local party leadership must reckon in the pursuance of its undertakings.
Undergraduate thesis (B.A.S.S. Political Science)-- University of the Philippines, Tacloban.
Keywords: Social science